Architects of world history researching the global past - Curtis, Kenneth R.; Bentley, Jerry H. (Wiley-Blackwell, 2014)
Architects of World History presents an innovative collection of original essays by leading scholars associated with World History, exploring through intellectual autobiography the ideas, challenges, and inspirations that are shaping the field. Features original, accessible contributions from pioneering scholars in the field. Offers insights into the process of developing a workable world history research topic and the experience of professional life as a world historian. Points to methodological challenges; the scholar's current research agenda in relation to the development of world history; and future directions anticipated for key areas within world history-- Provided by publisher.